2020
DOI: 10.1177/2158244020963668
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Small-Scale Miners on Interventions to Eradicate Illegal Small-Scale Mining in Ghana

Abstract: The proliferation of illegal mining in Ghana, coupled with its environmental impacts, especially on water bodies has compelled the government to ban all artisanal small-scale mining (ASM) activities in the country. The ban is intended to promote environmental sustainability while the government takes steps to provide sustainable health, and environmental-friendly ASM in Ghana. This paper assesses the perception of registered miners on the current approach by the Ghanaian government to stop illegal mining. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Following an interest in introducing appropriate governance in ASM, the Ethiopian ASM formalization strategy was developed in accordance with a pre‐context guideline developed by the international Intergovernmental Forum on Mining, Minerals, Metals, and Sustainable Development (IGF, 2017). And the latest study conducted by Wireko‐Gyebi et al (2020) on managing ASM also found agreement with the IGF's proposed “three‐phase of developing an ASM management strategy.” However, both proposed development models require the identification of stakeholders in the sector at the beginning of the development process. That can be difficult because only with the help of sector elements, the connections between partners across the sector can be mapped to identify the stakeholders.…”
Section: Introductionsupporting
confidence: 59%
“…Following an interest in introducing appropriate governance in ASM, the Ethiopian ASM formalization strategy was developed in accordance with a pre‐context guideline developed by the international Intergovernmental Forum on Mining, Minerals, Metals, and Sustainable Development (IGF, 2017). And the latest study conducted by Wireko‐Gyebi et al (2020) on managing ASM also found agreement with the IGF's proposed “three‐phase of developing an ASM management strategy.” However, both proposed development models require the identification of stakeholders in the sector at the beginning of the development process. That can be difficult because only with the help of sector elements, the connections between partners across the sector can be mapped to identify the stakeholders.…”
Section: Introductionsupporting
confidence: 59%
“…Artisanal goldminers, in this case are liable for their own health-care due to the nature of their occupation. Despite these evidences, most studies have focused on unsafe health, safety and environmental practices and its impacts (see Bansah et al., 2018 ; Lynas, 2018 ; Stewart, 2019 ; Wireko-Gyebi et al., 2020 ), risk perception (see Adeyemi and Olagunju, 2017 ; Antabe et al., 2017 ; Nunfam et al., 2019 ; Fadlallah et al., 2020 ) and economic impacts of artisanal mining (see Orleans-Boham et al., 2020 ; Zolnikov, 2020 ; Baffour-Kyei et al., 2021 ). No study, however, has investigated the complexities in self-care culture and how to improve it in the sector.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of artisanal small-scale mining in Ghana, coupled with its environmental impacts, especially on water bodies has compelled (responded to media report) the Government of Ghana to ban all artisanal smallscale mining (ASM) activities in the country from March 2017 [3]. This culminated in the setting up of Operation Vanguard, the largest centralised military-police joint task force to combat artisanal small-scale mining.…”
Section: Introductionmentioning
confidence: 99%
“…This ban lasted for almost two years and was lifted in December 2018 [4]. The ban was intended to promote environmental sustainability while the government takes steps to provide sustainable health and environmentally-friendly artisanal small-scale mining in Ghana [3]. However, the ban affected livelihood of the people in the district [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation